2019
DOI: 10.1111/scd.12357
|View full text |Cite
|
Sign up to set email alerts
|

Oral diseases and inflammatory burden and Alzheimer's disease among subjects aged 75 years or older

Abstract: Aim To study whether dental caries, periodontal disease, and stomatitis, and the related inflammatory burden associate with diagnosed Alzheimer's disease (AD) and dementia among older people. Methods The study population included 170 individuals aged ≥75 years. The primary outcome was diagnosed AD and the secondary outcome was any types of diagnosed dementia. Information about participants’ oral diseases and the related inflammatory burden was based on the clinical oral examination. Relative risks (RRs) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…A study where the proportion of periodontitis in different groups was based on scores of the digit symbol substitution test (DSST) [ 43 ] was excluded, and a study using the mean score of symbol digit substitution test (SDST) [ 44 ] in different groups based on periodontitis was also excluded. Finally, 8 case-control studies [ 27 , 32 , 45 , 46 , 47 , 48 , 49 , 50 ], 4 cross-sectional studies [ 24 , 25 , 51 , 52 ] and 8 descriptive studies [ 20 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were included in this study. The search and screening process of articles are displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study where the proportion of periodontitis in different groups was based on scores of the digit symbol substitution test (DSST) [ 43 ] was excluded, and a study using the mean score of symbol digit substitution test (SDST) [ 44 ] in different groups based on periodontitis was also excluded. Finally, 8 case-control studies [ 27 , 32 , 45 , 46 , 47 , 48 , 49 , 50 ], 4 cross-sectional studies [ 24 , 25 , 51 , 52 ] and 8 descriptive studies [ 20 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were included in this study. The search and screening process of articles are displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Further, three studies examined periodontal status by uniting the CPI with other oral health indexes, such as the GI [ 47 , 56 ], PI [ 47 ] and the GBI [ 55 ]. One diagnosed periodontitis with only PPD [ 58 ]. Another three papers used PPD and CAL as their periodontitis indexes [ 32 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude hazard ratio of dementia according to the number of remaining/lost teeth was 1.6 [10,34]. Tiisanoja et al [68] demonstrated that subjects with pocket depth ≥4 mm had an increased, but not statistically significant, risk of developing Alzheimer’s Disease (Relative risk: 1.54). Furthermore, Yoo et al [35] demonstrated that periodontal treatment lead to a significant decrease in the incidence of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, the probable causes of the loss of dental elements can be indicated in the elderly suffering from dementia by a gradual abandonment of the oral hygiene maneuvers and by the abandonment of dental care [22].…”
Section: Introductionmentioning
confidence: 99%